Examinations in Saint Lucia - Saint Lucia. Ministry of Education, Resource Development, Youth and Sports. Education Evaluation and Examination Unit (Caribbean Examination Council (CXC), 2000)
This paper presents an overview of the education system and briefly describes the administration of examinations in Saint Lucia.
Inaugural Conference of Caribbean Examination Bodies: Global Trends in Educational Assessment: Challenges and Opportunities for the Caribbean, Barbados, March 22-24, 2000